MECHANISMS OF RECEPTOR-DEPENDENT REGULATION OF BILE ACID AND XENOBIOTIC METABOLISM. THE ROLE OF CYP3A4 EXPRESSION IN THE SAFETY AND EFFECTIVENESS OF PHARMACOTHERAPY - Kubiak-Tomaszewska, Grażyna; Pachecka, Jan; Łukaszkiewicz, Jacek; Tomaszewski, Piotr (Prospects in Pharmaceutical Sciences, 2016)
The isoenzyme CYP3A4 is an important monooxygenase responsible for the metabolism of a large variety of endogenous and exogenous compounds (xenobiotics), including more than 50% of known drugs. The highest activity of CYP3A4 in human was found in hepatocytes and enterocytes. CYP3A4 gene expression is regulated by diverse exogenous and endogenous factors, including bile acids and several drugs, acting via nuclear receptors, such as, for example, PXR or FXR. Understanding the mechanisms of CYP3A4 gene expression is essential for ensuring the safety and effectiveness of pharmacotherapy. KEYWORDS: CYP3A4, expression, regulation, nuclear receptors, PXR, FXR, xenobiotic biotransformation, drug metabolism, bile acids, pharmacotherapy